Comparison of breeding objectives across countries with application to sheep indexes in New Zealand and Ireland. (April 2015) - Santos, B.F.S.; McHugh, N.; Byrne, T.J.; Berry, D.P.; Amer, P.R.
Summary Breeding objectives and selection indexes underpin the direction, the extent and the economic implications of selection in livestock populations under specific production systems. The objective of this study was to describe the methodology to calculate correlations between national selection indexes and gain a deeper understanding of the factors influencing responses in economically important traits in both the New Zealand and Irish sheep industries. Moderate to strong correlations were calculated among indexes within and between countries, with the strongest correlation (0.86) between the New Zealand and Irish maternal indexes. In both countries, responses to selection in the maternal indexes are largely driven by growth traits; each index, however, has a different balance of traits. Ewe mature weight also accounts for an important proportion of overall response and has significant emphasis in both maternal indexes. The majority of emphasis in terminal indexes of both countries is on growth and meat traits. Results from this study indicate that differences between national breeding objectives are unlikely to be a barrier to exchange of gene stocks among countries. Future research should investigate the extent to which genotype‐by‐environment (G×E) interactions exist at the level of individual traits. The methodology presented in this study is robust and represents an opportunity to inform the potential merits of international exchange of germplasm.